Mitotic and Meiotic Gene Conversion of Ty Elements and Other Insertions in Saccharomyces Cerevisiae - Vincent, A. (1989)
We examined meiotic and mitotic gene conversion events involved in deletion of Ty elements and other insertions from the genome of the yeast Saccharomyces cerevisiae. We found that Ty elements and one other insertion were deleted by mitotic gene conversion less frequently than point mutations at the same loci. One non-Ty insertion similar in size to Ty, however, did not show this bias. Mitotic conversion events deleting insertions were more frequently associated with crossing over than those deleting point mutations. In meiosis, conversion events duplicating the element were more common than those that deleted the element for one of the loci (HIS4) examined.